Resources, firms, and strategies - Foss, Nicolai J. (Oxford University Press, 1997)
Strategic management has been increasingly characterized by an emphasis on core competences. Firms are advised to divest unrelated businesses and return to core business. Moreover, competitive advantage is now increasingly seen as a matter of efficiently deploying scarce knowledge resources to product markets. Much of this change in emphasis has occurred because of the emergence of a unified and rigorous approach to strategy, often called the resource-based approach. This Reader brings together extracts from the seminal articles that created this dominant perspective in strategic management. It includes the pioneering work of Selznick, Penrose, and Chandler and more recent writing by Wenerfelt, Barney, Teece, and Prahalad and Hamel